The Effect of Variations in Centrifugation Time and Speed on the Quantity of Soil Transmitted Helminth (STH) Eggs - Abdul Ghofur; Kurniasih Wijayanti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Soil Transmitted Helminth (STH) infection is a significant health problem in Indonesia with a prevalence of 28.12%. Diagnosis of worm infections requires accurate detection, one of which is by the sedimentation method. The results of this sedimentation method are influenced by variations in centrifugation time and speed. This study aims to determine the effect of centrifugation time of 3, 5, and 10 minutes at a speed of 2500 rpm on the quantity of STH eggs. This study design is quasi-experimental using STH positive fecal samples from the Parasitology Laboratory of the Pekalongan Health Analyst Academy. The results showed a total of 12 eggs at 3 minutes, 18 eggs at 5 minutes and 24 eggs at 10 minutes, the Friedman test results (p = 0.264 > 0.05) mean there is no significant effect between variations in time and centrifugation speed on the quantity of STH eggs